Method of scheduling and active queues management on routers interfaces of telecommunication networks - Lebedenko, T. (ХНУРЕ, 2020)
The subject matter of the article is the method of scheduling and active queues management on routers interfaces of telecommunication networks. The goal of the work is to develop and improve the method related to the optimization of queues management processes on routers interfaces of telecommunication networks and aimed at improving the indicators of the quality of service. The article solves optimization problems of Congestion Management, Resource Allocation and Congestion Avoidance on routers interfaces of telecommunication networks in the framework of the two-stage calculation method. Research methods are based on the results of analytical calculations obtained in the course of using the Optimization Toolbox package of the Mat lab environment. Wherein in the course of improving the queue management method on routers interfaces of telecommunication networks, a mathematical programming apparatus was used, containing linear programming functions. The following results were obtained – the improved method of scheduling and active queues management on routers interfaces of telecommunication networks with the coordinated, sequential and two-stage solution of such interface problems as Congestion Management, Resource Allocation, and Congestion Avoidance. Conclusions: using the proposed method of scheduling and active queue management had made to achieve an agreed solution to Congestion Management, Resource Allocation, and Congestion Avoidance problems. In the course of solving the optimization problem of Congestion Management, which was conditionally related to the first stage of calculations, it was possible to achieve optimal aggregation and allocation of packet flows over queues formed on the router interface based on the commensurability of their classes. In the course of solving the optimization problems of resource allocation, and congestion avoidance, which were conditionally related to the second stage of calculations, it was possible to achieve an optimal bandwidth allocation of the router interface between the queues formed on it, and minimize possible denials of service.
Keywords: active queues management; congestion management; resource allocation; congestion avoidance; bandwidth; router interface; telecommunication network; quality of service